Nxhl Controls Angiogenesis by Targeting VE-PTP Through Interaction With Nucleolin - Luo, Honglin; Zhang, Yongde; Deng, Yanfei; Li, Lequn; Sheng, Zhaoan; Yu, Yanling; Lin, Yong; Chen, Xiaohan; Feng, Pengfei (Frontiers in Cell and Developmental Biology, 2021)
Precise regulation of angiogenesis is required for organ development, wound repair, and tumor progression. Here, we identified a novel gene, nxhl (New XingHuo light), that is conserved in vertebrates and that plays a crucial role in vascular integrity and angiogenesis. Bioinformatic analysis uncovered its essential roles in development based on co-expression with several key developmental genes. Knockdown of nxhl in zebrafish causes global and pericardial edema, loss of blood circulation, and vascular defects characterized by both reduced vascularization in intersegmental vessels and decreased sprouting in the caudal vein plexus. The nxhl gene also affects human endothelial cell behavior in vitro. We found that nxhl functions in part by targeting VE-PTP through interaction with NCL (nucleolin). Loss of ptprb (a VE-PTP orthologue) in zebrafish resulted in defects similar to nxhl knockdown. Moreover, nxhl deficiency attenuates tumor invasion and proteins (including VE-PTP and NCL) associated with angiogenesis and EMT. These findings illustrate that nxhl can regulate angiogenesis via a novel nxhl–NCL–VE-PTP axis, providing a new therapeutic target for modulating vascular formation and function, especially for cancer treatment.